2020
DOI: 10.1111/gwao.12515
|View full text |Cite
|
Sign up to set email alerts
|

Interfaces of domestic violence and organization: Gendered violence and inequality

Abstract: Funding informationSociety for the Advancement of Management Studies Domestic violence is a global pandemic. Domestic violence is gendered violence and perpetuates women's inequality.Women experience domestic violence at higher rates than men, and the perpetrators are, more often than not, men.Organizations play an essential role in addressing domestic violence. This article establishes the relationship between domestic violence and organizations at four interfaces of contemporary relevance, to make visible th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 71 publications
(101 reference statements)
0
25
0
1
Order By: Relevance
“…The study found that training is relevant and needed but also more efforts need to be in place to overcome the barriers that counselors and DVA practitioners may face to be competent and confident at supporting clients and their families. Significantly, the identification of these barriers need to be given strong consideration at an organizational level to ensure that domestic violence practitioners can carry out their work, as stated by Wilcox, Grenwood, Pullen, O'Leary, and Jones (2019) organizations have the responsibility to enact a duty of care for their employees, particularly in the field of domestic violence, discrimination and gender equality both inside and outside the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that training is relevant and needed but also more efforts need to be in place to overcome the barriers that counselors and DVA practitioners may face to be competent and confident at supporting clients and their families. Significantly, the identification of these barriers need to be given strong consideration at an organizational level to ensure that domestic violence practitioners can carry out their work, as stated by Wilcox, Grenwood, Pullen, O'Leary, and Jones (2019) organizations have the responsibility to enact a duty of care for their employees, particularly in the field of domestic violence, discrimination and gender equality both inside and outside the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Having the knowledge base to identify DVA will ensure early identification and intervention of these type of incidents and more women and their families can be supported as early and effectively as possible. Overall, this article is based on the importance of further training in the field of domestic violence as a direct increase in the demands for services; however, it acknowledges the need for a transformation of major socio‐political issues and inequalities that generate and enable domestic violence in the first instance (Wilcox et al, 2019). This much needed change requires the coordinated efforts of domestic violence organizations in the first instance but also other organizations, society and the government to eradicate gender inequalities and heightened vulnerabilities (Wilcox et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with previous years, domestic violence was up 54% in 2011 and 47% in 2013 (General Secretariat for Gender Equality, 2013). A rise in the incidents of domestic violence against women has also been reported during lockdown and the Covid‐19 pandemic (Mittal and Singh, 2020; Peterman et al., 2020; Wilcox et al., 2020).…”
Section: Introductionmentioning
confidence: 98%
“…By going to the local pharmacy, women could use the code word “Mask‐19” to let others know that they experience violence at home or sexual assault. This initiative aims to provide women a tool through which they will resist and reverse conditions of domination and cruelty intensified during the pandemic: “by thinking about women's agency to resist the position assigned to them, agency is back in the hands of women, and this is a refusal to give in to the ways patriarchy works on women” (Wilcox et al., 2020, p. 13).…”
Section: Introductionmentioning
confidence: 99%
“…For the purposes of this research, the term “DV” is used to refer to all types of violence (physical, verbal, sexual and psychological, including coercive control). Extant DV literature focuses on intimate partner and marital relationships (Bhat & Ullman, 2014; Devries et al., 2014), and women, generally the victims, are referred to as battered women, while their male partner is usually the DV perpetrator (Wilcox et al., 2021; Wong et al., 2011). Common forms of DV include physical violence, sexual abuse, emotional and financial mistreatments, utilized by the male perpetrator to exert control over their victim (Williamson, 2010).…”
Section: Introductionmentioning
confidence: 99%